Worm control for small ruminants in tropical Asia - Sani, R.A.; Gray, G.D.; Baker, R.L. (Australian Centre for International Agricultural Research, 2004)
ACIAR funded a collaborative project between research organisations in Southeast Asia for ILRI and regional partners to explore new ways to control helminth parasites in the tropics. The project aimed to increase small ruminant production in Southeast Asia by controlling internal parasites, which are one of the major constraints to sheep and goat production in the tropics. Control of internal parasites also provides an avenue for general improvement in husbandry methods. The three objectives of the project are: to prevent the spread of resistance to anthelmintics (dewormers) used for control of nematode parasites of sheep and goats in Asia; to assess genetic variation in resistance to gastrointestinal nematode parasites in different breeds of sheep and goats; and to disseminate information about control of internal parasites in the tropics. This publication and the accompanying CD draw together information from a number of sources to describe the state of research and development on worm control in sheep and goats in Asia and the Pacific. Topics of discussion include worm control; economic impacts of worm control; integrated approaches to sustainable parasite control; anthelmintic resistance; appropriate breeds and breeding schemes; options to overcome worm infection; impact of parasitism on the development of small ruminant populations; worm control methods; improving small ruminant productivity; and prevalence of internal parasites.